2013
DOI: 10.1111/iji.12066
|View full text |Cite
|
Sign up to set email alerts
|

Genetic connections among Turkic‐speaking Iranian ethnic groups based on HLA class II gene diversity

Abstract: Iran is a linguistically heterogeneous nation where Persian, Turkic and Arabic are the three main language families spoken. Based on their linguistic properties, Qashqais, Turkmens and Azeris are Turkic-speaking people. The purpose of this study was to investigate whether any genetic relationship exists among the Turkic-speaking Iranian subpopulations based on HLA class II gene diversity. HLA-DRB1, DQA1 and DQB1 alleles were identified by PCR-based methods in 100 Qashqais and 66 Turkmens, and the results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Although the results of HLA typing of UCB samples from the Royan Public CBB showed that the most frequent HLA alleles were similar to those in reports from different parts of Iran [18,19], the results of PCA revealed that the Royan Public UCB samples were closest to those of the Pars and Zoroastrian groups, and relatively far from those of other ethnic groups in Iran.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Although the results of HLA typing of UCB samples from the Royan Public CBB showed that the most frequent HLA alleles were similar to those in reports from different parts of Iran [18,19], the results of PCA revealed that the Royan Public UCB samples were closest to those of the Pars and Zoroastrian groups, and relatively far from those of other ethnic groups in Iran.…”
Section: Discussionsupporting
confidence: 70%
“…To determine the genetic relationship among UCB samples from the Royan Public CBB and 884 unrelated healthy samples from 13 ethnic groups in Iran [18,19], principal component analysis (PCA) was done with MVSP v. 3.1 software [20] using Nei's genetic distances (D A ) based on HLA-DRB1 allele frequencies, calculated with DISPAN software [21]. …”
Section: Methodsmentioning
confidence: 99%
“…The geographical separation and different historical origins of these ethnic groups play a significant role not only in building specific languages, cultures and life styles but possibly also has a bearing on their varied genetic background. However, some reports claim that common genetic roots of the ethnicities present in Iran are not changed significantly by encounters with other races throughout history (Farjadian & Safi, 2013). As the objective of the Iranome project was to develop a population-specific framework of genomic variations, providing a good resource for classifying these differences and producing reasonable national health care plans, we decided to include 100 individuals from each of the following ethnic groups: Arabs, Azeris, Baluchs, Kurds, Lurs, Persians, Turkmen, and also Persian Gulf Islanders (Figure 1b).…”
Section: Project Design and Selection Of Samplesmentioning
confidence: 99%
“…UC is a genetically and clinically heterogeneous group of disorders and millions of minorities from various ethnic, religious, and linguistic backgrounds also reside in Iran. So, these contradictory results can be due to the ethnic dependency of this study . Another reason for this discrepancy could be due to the small number of subjects in the present study.…”
Section: Resultsmentioning
confidence: 60%
“…Iran is one of the largest and most populated countries in the Middle East. It is a country with diverse ethnicities, among these groups are ethnic Fars, Turks, Lurs, Balouch, Azeri, Bakhtiari, Zoroastrian, Arabs, and Kurds . In UC patients, the colon is influenced by the excess and inappropriate responses of the immune system and limited inflammation to the colon .…”
Section: Introductionmentioning
confidence: 99%